METALLARNI KORROZIYADAN HIMOYA QILISH: ZAMONAVIY QOPLAMA TEXNOLOGIYALARI - Egamnazarova , F.D (Innovative Development in Educational Activities, 2023)
People use a lot of different materials, the list is huge. Metals are one of the most common materials used everywhere and for various purposes. In addition, there are a large number of metals (if you count alloys), all of which have their own advantages and disadvantages. One of the main disadvantages is corrosion, which destroys metals. We call it "rusting". And in this article, we will talk in detail about the causes of corrosion, which metals are more prone to it, and most importantly, how to protect them from it.